Preparation for Working Readiness Vocational Education Graduate with Self-Concept and Self-Efficacy Development - Novi Trisnawati (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
This article aims to examine the efforts that need to be done in facing the readiness of the working world for vocational education by developing self-concept and self efficacy. The increasingly intense work competition in the current era makes vocational education graduates should prepare themselves to be better prepared in facing the world of work. This is done by developing self-concept that can be formed through the planting of strong religious values, self-confidence, self-acceptance. The more we have a positive self-concept then success will be as expected. Self-efficacy is a physiological and emotional condition, expected to increase the ability to work and adapt to the work environment more easily, because self efficacy shows the implementation of processes that have been done during the previous learning process.